A new family of neotropical freshwater fishes from deep fossorial Amazonian habitat, with a reappraisal of morphological characiform phylogeny (Teleostei: Ostariophysi). Issue 1 (11th August 2017) - de Pinna, Mário; Zuanon, Jansen; Rapp Py-Daniel, Lucia; Petry, Paulo
Abstract: We present the taxonomic description of Tarumaniidae, a new family of South American freshwater fishes including a new genus ( Tarumania ) and species ( Tarumania walkerae ) from the Central Amazon. The new taxon displays an extraordinary set of unique characteristics, which sets it apart from all other known bony fishes, either in South America or elsewhere. Tarumaniidae has reverse-imbricated scales on the head, 244 or more scales along the midlateral lateral series, an 11-chambered swimbladder extending along most of the body, an anteriorly deflectable pelvic fin and a platybasic skull, among other unusual traits. Although the general habitus of Tarumania gives little hint of its phylogenetic placement, examination of internal anatomy is largely elucidative concerning the main features of its relationships. For example, Tarumania has a complete Weberian apparatus, comprising a set of characteristics supporting its position in Otophysi and Ostariophysi. Additional comparative evidence corroborates its placement in the order Characiformes, including some trademark characiform synapomorphies such as the presence of a hypertrophied lagenar capsule. We conducted a phylogenetic analysis on the basis of previously published morphological evidence for Characiformes, with the inclusion of Tarumania and additional relevant taxa and characters. Results support the position of Tarumania as a part of the superfamily Erythrinoidea and sister group to the neotropical Erythrinidae. Our increased taxonomic representation of Erythrinidae in the matrices firmly corroborates Tarumania as sister group to the whole of Erythrinidae and not to a subgroup of that family. Tarumania walkerae is a predator, which inhabits vast leaf-litter deposits in the Rio Negro drainage, and is found deeply buried in isolated pools during the dry season. It is the first characiform with an anguilliform body shape and fossorial habits. The unprecedented combination of phenotypic traits, behaviour and habitat adds substantially to the larger picture of freshwater fish diversity. Although its microhabitat is difficult to sample, the geographical range of T. walkerae includes areas close to major urban centres and which have been ichthyologically surveyed for many years. The fact that a relatively large and highly distinctive fish such as Tarumania remained undiscovered until now is testimony to the still-incomplete state of knowledge of biodiversity in Amazonian waters.